The marginalised mainstream : the culture of subcultural media 'journalists' in Singapore - Sim, Jui Liang (2014)
Technological changes including the invention of the Internet and the subsequent transformation of passive media consumers into active content producers have rendered porous the boundaries of journalism. Yet studies on journalists in Singapore have been largely confined to professionals working in mainstream media organisations. Elsewhere, studies have been conducted on independent or alternative journalists who operate outside of mainstream media structures. However, most of them tend to be involved in radicalised political media, citizens media or community media. Little is known about the culture of the individuals working in subcultural media which is produced by members of a particular subculture and aimed at serving the needs of that subculture. Hence, this study seeks to contribute to the discussion on the culture of journalists in Singapore by focusing on writers and editors who not only work outside mainstream media, but are also involved in subcultural media.